Recent Advancement in Remote Sensing Technology for Hydrology Analysis and Water Resources Management - Weili Duan; Shreedhar Maskey; Pedro L. B. Chaffe; Pingping Luo; Bin He; Yiping Wu; Jingming Hou (Remote Sensing, 2021)
Water is undoubtedly the most valuable resource of human society and an essential component of the ecosystem [...]